Death Penalty for Ferdy Sambo In Human Rights Perspective (Non Derogable Right Vs Derogabel Right) - Agus Bambang Nugraha*; Fadil Mas’ud; Sudiyarti Sudiyarti; Achmad Napis Qurtubi; Egidius Fkun (Universitas Syiah Kuala, 2023)
The Supreme Court judge canceled the death sentence for Ferdy Sambo to life imprisonment. This has caused controversy in the community. One side considers the Supreme Court decision to be unfair and on the other hand considers it fair because the right to life is a basic human right and cannot be reduced under any circumstances and under any circumstances. This research is a qualitative research with a fenomenolgy approach. The data used in this study is secondary data obtained from journals, books, websites and other reliable sources. The data collected was analyzed using several stages including observation, selection, and drawing conclusions. The results showed that the change in the decision on Ferdy Sambo's death sentence to life imprisonment was appropriate because the researchers agreed that the right to life is a right that cannot be limited under any circumstances and under any circumstances.